Komunikasi Antarpribadi Front Desk untuk Peningkatan Layanan Prima di Universitas Terbuka Serang - Dirasful, Zetriwan; Hadiati, Hadiati; Handayani, Mediana (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This study aims to analyze the role of interpersonal communication conducted by front desk staff in improving service quality at Universitas Terbuka Serang. Using a qualitative approach with a phenomenological design, the study explores the experiences and perceptions of both students and service staff. Data were collected through in-depth interviews, participant observation, and document analysis. The findings indicate that aspects such as openness, empathy, supportive attitudes, positivity, and shared backgrounds in communication significantly contribute to enhancing student satisfaction. Openness in providing information and empathy from staff in addressing student needs create a more inclusive and supportive service environment. Supportive and positive attitudes from front desk staff strengthen interpersonal relationships and improve service efficiency. Shared backgrounds between staff and students facilitate more effective communication and expedite problem resolution. These findings suggest that implementing interpersonal communication strategies that consider these factors can enhance the quality of academic services. Recommendations for Universitas Terbuka Serang include regular training for front desk staff and the routine collection of student feedback for continuous improvement.